Regulation of Cancer Cell Responsiveness to Ionizing Radiation Treatment by Cyclic AMP Response Element Binding Nuclear Transcription Factor - D’Auria, Francesca; Centurione, Lucia; Centurione, Maria Antonietta; Angelini, Antonio; Di Pietro, Roberta (Frontiers in Oncology, 2017)
Cyclic AMP Response Element Binding (CREB) protein is a member of the CREB/ATF (Activating Transcription Factor) family of transcription factors that play an important role in the cell response to different environmental stimuli leading to proliferation, differentiation, apoptosis and survival. A number of studies highlight the involvement of CREB in the resistance to ionizing radiation therapy, demonstrating a relationship between ionizing radiation-induced CREB family members activation and cell survival. Consistent with these observations, we have recently demonstrated that CREB and ATF-1 are expressed in leukemia cell lines and that low dose radiation treatment can trigger CREB activation leading to survival of erythro-leukemia cells (K562).. On the other hand, a number of evidences highlight a pro-apoptotic role of CREB following ionizing radiation treatment of cancer cells. Since the development of multiple mechanisms of resistance is one key problem of most malignancies, including those of hematological origin, it is highly desirable to identify biological markers of responsiveness/unresponsiveness useful to follow-up the individual response and to adjust anticancer treatments. Taking into account all these considerations, this mini-review will be focused on the involvement of CREB/ATF family members in response to ionizing radiation therapy, to deepen our knowledge of this topic and to pave the way to translation into a therapeutic context.